Overweight, obesity and abdominal obesity in the adult population of Peru - Pajuelo Ramírez, Jaime (2019)
Introduction. Obesity is a public health problem; the objective of the present study was to determine the national prevalence and distribution of overweight (S), obesity (O) and abdominal obesity (OA), in Peru. Methods. An observational study was conducted through the analysis of the National Household Survey 2012-2013 in which 20488 adults were evaluated. The nutritional diagno≥sis was determined considering the thWeHO eva boluatidy maon oss if OndeA thx: 1e 8wa,5ist toc 2i4rc,9u nmfeo rermalnc, 2e 5≥ to 10 <32 c0 ovem for merweighn at, and nd ≥ 88 to c 3m fo0 kg/m2r wo omebensi waty. Ls ciokensiwidesere, fod.r Results. The national prevalence of overweight was 40,5% and obesity 19,7%, with a total of 60,2% of adult population with excess weight. 23,4% of O were women and 15,7% were men; OA in women was 51,2% and 14,8% in men. The departments with the highest prevalence of excess weight were Tacna (73,8%) and Ica (72,2%). The departments with the highest prevalence of OA were Lima, Ica and Lambayeque, with prevalences higher than 40%. There was a higher prevalence of O and OA in people older than 40 years, in a population living on the coast, less than 1000 meters above sea level and residing in urban areas. Conclusions. 60,2% of peruvian adult population presented excess weight (S and O), predominantly in Tacna and Ica, increasing the prevalence with respect to what was previously reported.